QORAQALPOQ TA’LIMIY KORPUSINI YARATISHNING NAZARIY ASOSLARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article will focus on the educational building, its significance, and the theoretical foundations of the creation of the Karakalpak educational building. We will also talk about the importance of the Karakalpak educational building and the effectiveness of training.
Keywords: Corpus, language Corpus, text corpus, educational Corpus, National Corpus, electronic library, e-learning dictionaries.